Peranan juruaudit dalam hubungan di antara kompleksiti dan kelewatan audit bagi syarikat-syarikat yang tersenarai di Bursa Malaysia - Azliana, Seliman (2018)
Audit report is an important source of information that is used by investors, shareholders, bankers, trade creditors, governments, and the public. Therefore, delays in the issuance of financial statements should be avoided so that stakeholders can use the information contained in the financial statements in a timely manner to make important decisions. This study investigates the influence of auditors in the relationship between business complexity and audit delay among Malaysian listed companies on the main markets and the ACE market by using secondary data from Bursa Malaysia. Audit delay is measures based on the difference in number of days between the closing date of the company account were closed to the date of the external auditor's report issued. This study covers 349 listed companies on Bursa Malaysia for 2015 and 2016 (N = 698). It was found that the companies, on average, took more than three months to release their financial reports. The findings show that auditor type, number of subsidiaries, leverage, sign of income and company size are significantly related to audit delay. While audit opinion and the proportion of receivables and inventory to total asset are insignificant towards audit delay. This study recommends that future studies use the actual time spent on auditing the company accounts and not based on the number of days taken to complete the audit work because by using real time in identifying audit delays will give the more accurate results.